MICROSCOPIC ANALYSIS THE GROWTH OF Azolla microphylla IN BRACKISH WATER - Daulay, Anita Diah Permata Sari; Effendi, Irwan; Feliatra, Feliatra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbtrakAzolla microphyllais a water fern that floats and rich of protein, essential amino acids, vitamins and minerals. The ferncan be found in ponds, ditches,warm temperature fields and tropical regions throughout the world. Research on microscopic analysis the growth of Azolla microphylla in brackish water was carried out from April to June 2018. A. microphylla was grown in containers with a volume capacity of 20 liters. The container was filled with planting media, then filled with brackish water to a volume of 10-15 liters and this ecosystem is set to 0 ‰, 1 ‰, 2 ‰ and 3 ‰. The growth of A. microphylla was observed by measuring biomass growth, colony growth, and double time growth, microscopic observations of leaves, rhizomes and rootsA. microphylla. From the results of the study it was found that A. microphylla can grew in brackish water (salinity 1‰, 2‰ and 3‰), however growth tends to be slower than in fresh water (salinity 0 ‰), and also can be seen based on the cross section of leaves, roots and rhizomes that grew optimally at salinity 0 ‰, and experience changes in shape and color in the cross section and do not grew optimally at salinity 1‰, 2‰ and 3‰.Keywords: Azolla microphylla growth, microscopic analysis, brackish water